A qualitative study on marriage reconciliation process under marriage tribunal in Malaysia - Mohd Zin, Najibah; Abdul Hak, Nora; Sowell, Sarafuddin Abdul Syahid (2017)
Statistic from National Registration Department of Malaysia shows that the divorce rate compared to the rate of marriage for non-Muslim and Muslim couples has increased steadily especially beginning the year 2001. Divorce rate in Malaysia for both Muslims and non-Muslims had increased from 11.24% in 2001 to 18.67% in the year of 2010. This indicates that the rate of divorce among the married couples is on rise every year in Malaysia. Divorce should be the last option resorted to by a marriage couple in solving marital dispute and it should be chosen when there is a necessity for such. Divorce may negativelyaffectthe life of the couple and the children. To avoid from unnecessary divorce, relevant authorities have implemented reconciliation process where effort is taken to reconcile the married couples and to amicably settle their dispute without going for divorce. However, the number of successful reconciliation between discorded estranged married couple is relevantly small. Hence, through series of interviews, this study is conducted with the aims to explore the issues during the reconciliation sessions and the perception of the couple on the reconciliation sessions which may lead to the understanding why the reconciliation process is a failure. It is hoped that this study and those earlier literatures on marriage reconciliation could shed lights to the question of effectiveness of current marriage reconciliation process and how it can be revamped for further improvement. Keywords: family law, divorce, reconciliation,